International conference and exhibition "Airdrome - 97" - Бєлінський, І. О.; Білеуш, А. І.; Шинкарчук, A. B. (Proceedings of National Aviation University (archive), 1998)
Considered are the results of the International scientific conference and exhibition "Airdrome - 97" dedicated to modem problems of aéroports construction, maintenance of special aéroports transport means, airdrome construction and airdrome maintenance technique